2011
DOI: 10.1021/jo2018312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Purity of Cucurbit[n]uril (n = 7, 8) Host Samples

Abstract: The formation of highly stable inclusion complexes in aqueous solution between the organometallic cobaltocenium cation (Cob(+)) and the hosts cucurbit[7]uril (CB7) and cucurbit[8]uril (CB8) was used to develop a simple method, based on UV-vis titrations, to assay the purity of samples of these two hosts. The equilibrium association constant (K) of the Cob(+)@CB7 complex had been previously reported by our group as 5.7 × 10(9) M(-1) at 25 °C in 50 mM sodium acetate medium. In this work, we determine a K value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 16 publications
(24 reference statements)
2
79
0
3
Order By: Relevance
“…Due to poor solubility of CB [8] in water and its hygroscopic nature, the apparent molecular weight of the commercial powder and its actual concentration in aqueous solutions were determined for each batch using a simple and highly reproducible method described previously. 47 FG6 Peptide. The FG6 peptide was a gift from Emanuela Cavatorta, produced by solid phase peptide synthesis and purified using reverse phase HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…Due to poor solubility of CB [8] in water and its hygroscopic nature, the apparent molecular weight of the commercial powder and its actual concentration in aqueous solutions were determined for each batch using a simple and highly reproducible method described previously. 47 FG6 Peptide. The FG6 peptide was a gift from Emanuela Cavatorta, produced by solid phase peptide synthesis and purified using reverse phase HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…[a] Concentration of CB[8] was spectrophotometrically determined 24. [b] See Figure 2 and text for details.…”
mentioning
confidence: 99%
“…Exact cucurbit [8]uril (Sigma Aldrich) concentration was determined by titration as described by Kaifer et al [69] Concentrations of WGG and methylviologen were confirmed by molecular absorption by making use of the theoretical extinction coefficient e 280 = 5500 m À1 cm À1 for WGG and the reported extinction coefficient e 257 = 20 400 m À1 cm À1 for methylviologen. [70] The WGG-YFP and MGG-YFP proteins were present in PBS buffer after purification.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%